MEMBANGUN NEGARA HUKUM DI ERA PEMERINTAHAN PRESIDEN JOKO WIDODO - Satriya, Bambang (Fakultas Hukum Universitas PGRI Kanjuruhan Malang, 2016)
President of the Republic of Indonesia Joko Widodo has many strategic constitutional authority in the world of law, so that with this authority, the President Jokowi able to determine the political development of a state of law. President Jokowi could make policy or rules that could affect the operation of state life was good. Instead, the state law could lose its authority, if the establishment of the rule does not reflect the interests of the law or just put the interests of others.